2007
DOI: 10.1007/s00531-007-0221-z
|View full text |Cite
|
Sign up to set email alerts
|

Late Cretaceous exhumation history of an extensional extruding wedge (Graz Paleozoic Nappe Complex, Austria)

Abstract: Late Cretaceous structures within the eastern Graz Paleozoic Nappe Complex define an extruding wedge with north-eastward directed thrusting in eastern portions and strike-slip shear along the margins. Stacking structures are overprinted by south-westward directed extension with low-grade metamorphic rocks in the hangingwall and highgrade basement rocks in the footwall. Pressure-temperature and structural data are obtained from successively opening quartz veins that record various stages of progressive deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Based on Sm-Nd ages on garnet cores and U-Th-Pb chemical dating on monazite, the Rappold Complex experienced a Permian metamorphic imprint (Rög-gla, 2007;Gaidies et al, 2008) and an Eoalpine (Cretaceous) overprint. Calculated P-T-conditions of the Permian garnet cores from the ACU are about 580±20°C at about 0.8 GPa (Rög-gla, 2007;Krenn et al, 2008) and are in agreement with conditions of the Rappold Complex in the Niedere Tauern mountain range (Faryad and Hoinkes, 2003;Gaidies et al, 2006). Du-______________________ ____________ __________________ Table 8: The structural distribution of cations after Spear and Kimball (1984) for the same amphibole analyses (given in Tab.…”
Section: -8 44 Rappold Complex (Radegund Nappe/acu)supporting
confidence: 59%
See 4 more Smart Citations
“…Based on Sm-Nd ages on garnet cores and U-Th-Pb chemical dating on monazite, the Rappold Complex experienced a Permian metamorphic imprint (Rög-gla, 2007;Gaidies et al, 2008) and an Eoalpine (Cretaceous) overprint. Calculated P-T-conditions of the Permian garnet cores from the ACU are about 580±20°C at about 0.8 GPa (Rög-gla, 2007;Krenn et al, 2008) and are in agreement with conditions of the Rappold Complex in the Niedere Tauern mountain range (Faryad and Hoinkes, 2003;Gaidies et al, 2006). Du-______________________ ____________ __________________ Table 8: The structural distribution of cations after Spear and Kimball (1984) for the same amphibole analyses (given in Tab.…”
Section: -8 44 Rappold Complex (Radegund Nappe/acu)supporting
confidence: 59%
“…The dotted square indicates the position of the map shown in Figure 1B. (B) Geological sketch map of the Graz Paleozoic and the underlying crystalline complexes (modified after Krenn et al 2008). The study area is indicated by the dotted square.…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations